PENERAPAN EQUAL EMPLOYMENT OPPORTUNITY BERDASARKAN RATIFIKASI KONVENSI ILO NO. 111 TERHADAP PENGHAPUSAN DISKRIMINASI GENDER (STUDI KASUS PADA BANK X CABANG KEDIRI) - Bimantari, Lovina (Jurnal Ilmiah Mahasiswa FEB, 2013)
The  aim  of this study  is  to determine how the application of  equal employment opportunity (EEO) by ratification of Convention of ILO No. 111 towards the elimination of gender discrimination in the  Bank X  Branch Kediri. This study used qualitative research methods  -  case study, the method used to reach,  explain and describe any problems with greater depth and in accordance with the problem and research objectives. This study uses three informants  as key persons, selected by  purposive and snowball sampling. The data analysis technique used is the analysis of the meaning (content analysis).  Data verification analyses used are construct validity, internal and external validity,  and reliability. The results of this study are not encountered discrimination against female workers in terms of: access to employment, access to training and development, access to appropriate positions gain increased experience, and the same wage. In the aspect of working conditions, provision of life and health insurance provided to employees of women are not equal to male employees Keywords: Equal Employment Opportunity, ILO No. 111, Gender Discrimination.